Dietary Inflammatory and Its Association with Cognitive Frailty Among Community-Dwelling Older Adults in Klang Valley - Bong Jun Fae, Felicia; Abdul Rahman, Rasyidah; Md Fadzil, Nurul Hidayah; Shahar, Suzana (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Dietary inflammation is a significant risk factor for age-related cognitive impairments among older adults. However, information related to the relationship between Empirical Dietary Inflammatory Index (eDII) score and cognitive frailty (CF) among Malaysian community-dwelling older adults is still limited. The objective of this study is to determine the association between dietary inflammatory risk and CF among community-dwelling older adults. Method: This is a cross sectional study involving community-dwelling older adults in Klang Valley. The Fried’s Criteria and Clinical Dementia Rating (CDR) were used to determine CF status. Subjects were also interviewed using the Dietary History Questionnaire (DHQ) and eDII food checklist to assess the food intake and dietary inflammatory risk. Data collected was analyzed using SPSS version 26.0. Results: A total of 158 older adults (66.7 ± 5.2 years old) residing in Klang Valley were involved. Energy and macronutrients have a weak positive association with pro-inflammatory score (p<0.05). There is no significant mean difference between CF older adults consumed a more pro-inflammatory diet (mean 2.07 ± 1.10) compared to non CF (mean 2.06 ± 1.14). However, white rice food item significantly consumed by CF people (22.4%) than non CF (8.5%) (p<0.05). Conclusion: CF older adults were more likely to consume a pro-inflammatory diet particularly from the rice food group. There is a need to further assess the risk of consuming a pro-inflammatory diet using larger sample size and appropriate biomarkers.